2018
DOI: 10.1093/mnras/sty2884
|View full text |Cite
|
Sign up to set email alerts
|

Wandering near the red edge: photometric observations of three cool ZZ Ceti stars

Abstract: We summarize our findings on three cool ZZ Ceti type pulsating white dwarfs. We determined eight independent modes in HS 0733+4119, of which seven are new findings. For GD 154, we detected two new eigenmodes, and the recurrence of the pulsational behaviour first observed in 1977. We discuss that GD 154 does not only vary its pulsations between a multiperiodic and a quasi-monoperiodic phase, but there are also differences between the relative amplitudes of the near-subharmonics observed in the latter phase. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Cool ZZ Cetis, near the red edge of the instability strip, show long pulsation periods, and those observed -i.e., with significant amplitude-in general change with time. Bognár et al (2018b) detected 14 frequencies for HS 0733+4119, of which 8 are independent modes; for GD 154, 17 frequencies, with 4 independent modes, and for R808, the 28 frequencies discussed in Thompson et al (2009) and 2 new ones.…”
Section: Recent Observational Achievementsmentioning
confidence: 96%
“…Cool ZZ Cetis, near the red edge of the instability strip, show long pulsation periods, and those observed -i.e., with significant amplitude-in general change with time. Bognár et al (2018b) detected 14 frequencies for HS 0733+4119, of which 8 are independent modes; for GD 154, 17 frequencies, with 4 independent modes, and for R808, the 28 frequencies discussed in Thompson et al (2009) and 2 new ones.…”
Section: Recent Observational Achievementsmentioning
confidence: 96%
“…It is definitely a great advantage for the present generation that they do not have to fight for the acceptance of the observed data. Comparative analyses of the observation of the subsequent years for GD 154 revealed that the star not only varied its pulsational behavior between a "simple" multi-periodic and a quasi mono-periodic phase with harmonic and subharmonic peaks, but there were differences between the visibility of the near-subharmonics in the latter phase (Bognár et al, 2019). GD 154 will be a target of TESS (private communication by Zs.…”
Section: Results Between 1970-1980mentioning
confidence: 99%
“…We accepted a frequency peak as significant if its amplitude reached the five signal-to-noise ratio (S/N), where the noise level was calculated by the average Fourier amplitude in a ∼1700 µHz radius vicinity (150 d −1 ) of the peak in question (see e.g. Bognár et al 2019b). That is, we used a higher significance level than the usual four S/N; we accepted the highest amplitude peaks as possible pulsational frequencies during the pre-whitening process of these targets showing complex pulsational behaviour, with several closely spaced peaks in their Fourier transforms (FTs).…”
Section: Light Curve Analysismentioning
confidence: 99%
“…With this publication on PM J22299+3024 and LP 119-10, we continue our efforts to introduce the results of our long-term ground-based observations on pulsating white dwarf stars in a series of papers (see e.g. Bognár et al 2009Bognár et al , 2014Bognár et al , 2016Bognár et al , 2019bPaparó et al 2013).…”
Section: Introductionmentioning
confidence: 99%